Progressive Aspect in Hijazi Arabic - Abdullah Ibrahim Alsubhi (الآداب للدراسات اللغوية والأدبية, 2024)
This paper aims to analyze and compare imperfective forms and implications in Hijazi Arabic, situated in the ongoing grammaticalization process of a progressive aspect marker across Arabic vernaculars. In Modern Standard Arabic, an eventive imperfective verb is ambiguous, as it could be given a progressive or a habitual reading. In the context of /min al-muhtamali ʔan/ “of the likely” however, it can only be given a future shifted reading. In Hijazi Arabic on the other hand, the study findings showed that eventive imperfective verbs are always ambiguous despite the context. With regard to the progressive aspect marker, it was revealed that Hijazi Arabic behaves like other dialects in that a marker has developed out of the active participle of the verb “sit” to indicate a progressive reading. Even though the newly developed marker in Hijazi Arabic does not require an animate subject and appears with verbs having seemingly conflicting meanings (e.g., “sit” used with “swim”), it has not lost its lexical meaning, and a short form has not been developed like in other dialects, such as Maltese and Iraqi Arabic.